Types of spices used in Bottle Masala - Mumbai Archive Project Team (Jio Institute, 2024)
The proportion and variety of spices used in bottle masala are closely guarded secrets passed down within the family. The ingredients range from popular spices like lal mirch (red chilli), tejpatta (bay leaf), dalchini (cinnamon), elaichi (cardamom), and javitri (mace) to rare spices like mugwort, stoneflower, and Nagkesar (cobra saffron). On average, 25–30 spices are used in a masala, but it can range from as few as 20 to as many as 50.